Exploring linkages between climate change and sexual health: a scoping review protocol - Logie, Carmen H; Toccalino, Danielle; Reed, Anna Cooper; Malama, Kalonde; Newman, Peter A; Weiser, Sheri; Harris, Orlando; Berry, Isha; Adedimeji, Adebola (BMJ open, 2021)
IntroductionThe effects of climate change and associated extreme weather events (EWEs) present substantial threats to well-being. EWEs hold the potential to harm sexual health through pathways including elevated exposure to HIV and other sexually transmitted infections (STIs), disrupted healthcare access, and increased sexual and gender-based violence (SGBV). The WHO defines four components of sexual health: comprehensive sexuality education; HIV and STI prevention and care; SGBV prevention and care; and psychosexual counselling. Yet, knowledge gaps remain regarding climate change and its associations with these sexual health domains. This scoping review will therefore explore the linkages between climate change and sexual health.Methods and analysisFive electronic databases (MEDLINE, EMBASE, PsycINFO, Web of Science, CINAHL) will be searched using text words and subject headings (eg, Medical Subject Headings (MeSH), Emtree) related to sexual health and climate change from the inception of each database to May 2021. Grey literature and unpublished reports will be searched using a comprehensive search strategy, including from the WHO, World Bank eLibrary, and the Centers for Disease Control and Prevention. The scoping review will consider studies that explore: (a) climate change and EWEs including droughts, heat waves, wildfires, dust storms, hurricanes, flooding rains, coastal flooding and storm surges; alongside (b) sexual health, including: comprehensive sexual health education, sexual health counselling, and HIV/STI acquisition, prevention and/or care, and/or SGBV, including intimate partner violence, sexual assault and rape. Searches will not be limited by language, publication year or geographical location. We will consider quantitative, qualitative, mixed-methods and review articles for inclusion. We will conduct thematic analysis of findings. Data will be presented in narrative and tabular forms.Ethics and disseminationThere are no formal ethics requirements as we are not collecting primary data. Results will be published in a peer-reviewed journal and shared at international conferences.